Channels of interaction and past collaborative experience as imperatives in academia–industry collaboration. Issue 10 (26th November 2017) - Bhullar, Supreet S.; Nangia, Vinay K.; Batish, Ajay
ABSTRACT: The present study deals with the engagement of academics with the industry using different channels for the transfer of knowledge and technology. The study provides empirical evidence substantiating the effect of the frequency of use of the different channels of interaction in explaining the relationship between past collaborative experience of the academic and the outcomes of academia–industry collaboration. The results indicate that past collaborative experience develops strong insights into industrial problems, opens up avenues for research projects, leads to industrial funding and builds research networks. The prospects of commercialisation of research of the academic are also rooted in past collaborative experience. The results also reveal that the frequency of use of the traditional and bi-directional channels partially mediate the relationship between the collaborative experience and the outcomes of collaboration, validating that higher collaborative experience leads to increased frequency of use of channels that results in improved outcomes of academia–industry collaboration.